Phase and isotope-geochemical hydrocarbon differentiations within the border interval bet ween a sedimentary cover and the Precambrian crys talline basement - Lukin, A.E. (Reports of the National Academy of Sciences of Ukraine, 2020)
The phase and isotope-geochemical hydrocarbon differentiations within the border interval including basal layers of a sedimentary cover and the upper edge of the Precambrian crystalline basement have been considered for first time (by the data of studies of the Yulievskoe oil-gas condensate field, Dnieper-Donets depression). The important role of this combined barrier (superposition of the geothermodynamic — geochemical — microbiogenic ores) in the processes of naphtidogenesis and oil-gas accumulation has been established.